Magnetic and electromagnetic treatment of the nutrient solution in arugula hydroponic cultivation - Tellez, Hayver Olaya [UNESP]; Putti, Fernando Ferrari [UNESP]; Boas, Roberto Lyra Villas [UNESP] (Univ Federal Goias, 2024)
Hydroponic cultivation is relevant in vegetable production due to the efficient use of resources, plant growth control, high yields and good quality of harvested products. This study aimed to assess the effects of magnetic and electromagnetic treatments of the nutrient solution on the hydroponic arugula production. The treatments comprised the exposition of the nutrient solution to magnetism, electromagnetism and conventional cultivation (control) monitored during four periods (7, 14, 21 and 28 days after transplanting), with four replicates for each treatment. The experiment followed a completely randomized factorial design. The magnetic treatment led to gains in plant growth and yield, in addition to reducing the presence of algae in roots, as well as increasing the concentrations of magnesium, manganese and iron in the development of the arugula crop under hydroponic cultivation, but with no direct effect on plant growth.
Keywords: Eruca sativa; hydroponic cultivation; plant nutrition